Analysis of project-based learning videos on biology subjects - Hartini Riudin; Kasman Arifin; Murni Sabilu (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
This study aims to analyze project-based learning videos on biology subjects on YouTube. This type of research is descriptive research with qualitative approach. The object of the research was a real teaching video about project-based learning in biology subjects on YouTube. The instrument in this research is an observation sheet that contains aspects of the activities carried out in project-based learning which have been validated by three learning experts. The data analysis technique used is descriptive analysis, by observing learning videos and evaluating through instrument, then the data is processed and classified into categories. The results of observations of four video real teaching project-based learning in biology subjects on YouTube are in the good and sufficient categories. Each video category is video 1 received a score of 85 which was classified as good category, the videos 2 and 3 scored 71 in the good category, and the video 4 scored 61 in the sufficient category.Abstrak Penelitian ini bertujuan untuk menganalisis video pembelajaran berbasis proyek pada mata pelajaran biologi di YouTube. Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan kualitatif. Objek penelitian berupa video real teaching mengenai pembelajaran berbasis proyek pada mata pelajaran Biologi di YouTube. Instrumen dalam penelitian ini berupa lembar pengamatan yang berisi aspek-aspek kegiatan yang dilakukan dalam pembelajaran berbasis proyek yang telah divalidasi oleh tiga pakar pembelajaran. Teknik analisis data yang digunakan adalah analisis deskriptif, dengan mengamati video pembelajaran dan dilakukan penilaian melalui instrumen, kemudian data diolah dan diklasifikasikan dalam kategori. Hasil pengamatan terhadap empat video real teaching pembelajaran berbasis proyek pada mata pelajaran biologi di YouTube berada pada kategori baik dan cukup. Masing-masing kategori video yaitu video 1 memperoleh nilai sebesar 85 tergolong kategori baik, video 2 dan 3 memperoleh nilai sebesar 71 tergolong kategori baik, dan video 4 memperoleh nilai sebesar 61 tergolong kategori cukup.